Assessing Quality of In-Patient Care and Patients's Expectations Using A SERVQUAL Approach in A Tertiary Care Hospital in India - Diwakar R; Jegan Joseph; Logaraj M; Kaveri Palanisamy; Manoj Punniyamurthy (Medsci Publications, 2024)
Background: Patient satisfaction is a key indicator of healthcare service quality and has implications for the growth and success of healthcare organizations. However, there is often a gap between patients' expectations and perceptions of service quality, which can vary depending on various sociodemographic factors. This study aimed to assess the expectations, perceptions and service quality gap in a tertiary care hospital using SERVQUAL model. Materials and Methods: A cross-sectional study was conducted among 120 adult inpatients using a semi-structured questionnaire based on the five dimensions of the SERVQUAL model. The quality gap was calculated as the difference between perception and expectation scores. Results: The study found a significant negative quality gap across all five dimensions, with the largest gaps observed in reliability and responsiveness. The study also revealed that gender, age, and education influenced patients' perception of service quality, while type of specialty, residence, monthly income, and occupation did not have a significant effect. Conclusion: The study highlighted the need for improving the service quality in the tertiary care hospital, especially in terms of reliability and responsiveness. The study also suggested that healthcare managers and providers should consider the diverse expectations and needs of patients based on their sociodemographic characteristics.